Complex presentation of adult-onset Still's disease. Issue 4 (25th April 2019) - Zafran, Muhammad; Wassef, Nancy
Abstract : A 61-year-old woman was admitted with feeling generally unwell with influenza-like symptoms, for almost a month. This was followed by dyspnoea, productive cough and fever of >40°C. She was started on oral antibiotics in community, but due to rising inflammatory markers, she was referred for admission to our hospital. Chest X-ray showed left basal pneumonia and SE was started on intravenous antibiotics according to microbiologist's advice. During admission she developed deranged liver functions with right upper quadrant tenderness, pleural and pericardial effusions. This was followed by multiple joint aches, mouth ulcers and a rash on her chest. Finally, after several days and clinical dilemma, she was diagnosed with adult-onset Still's disease by the rheumatologist and was started on prednisolone, to which she showed marked improvement, and was later maintained on methotrexate and hydrotherapy. She was in remission during her follow-up in the rheumatology clinic.